2004
DOI: 10.1002/pi.1630
|View full text |Cite
|
Sign up to set email alerts
|

Structure and property study of nylon‐6/clay nanocomposite fiber

Abstract: The crystal structures of nylon‐6 and nylon‐6/clay fibers were investigated on annealing and drawing. Annealing increased the γ‐crystalline form of both fibers, as indicated by the DSC curves, and its effect was dominant in nylon‐6/clay fiber. On drawing, the γ‐crystalline form was easily converted into the α form in nylon‐6, whereas it was still observed at a relatively high spin‐draw ratio in nylon‐6/clay fiber. However, although the α‐crystal form was dominant in nylon‐6, the γ‐crystal form was dominant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…[7] In his case, the N6CN was prepared using aminolauric acid-modified montmorillonite by in situ polymerization. A recent paper by Yoon et al also reported a 245 8C endothermal peak, having adopted a normal DSC to study a similar nanocomposite to that used by Kojima et al [19] Different starting materials, preparation methods, and measurement techniques provided clear evidence of a similar phenomenon. Apparently, the appearance of the high-temperature endothermal peak/peaks is the likely outcome of a strong interaction between the polymer chains and the nanodispersed silicate layers.…”
Section: Resultsmentioning
confidence: 99%
“…[7] In his case, the N6CN was prepared using aminolauric acid-modified montmorillonite by in situ polymerization. A recent paper by Yoon et al also reported a 245 8C endothermal peak, having adopted a normal DSC to study a similar nanocomposite to that used by Kojima et al [19] Different starting materials, preparation methods, and measurement techniques provided clear evidence of a similar phenomenon. Apparently, the appearance of the high-temperature endothermal peak/peaks is the likely outcome of a strong interaction between the polymer chains and the nanodispersed silicate layers.…”
Section: Resultsmentioning
confidence: 99%
“…The flammability of knitted structure made with PA6 and PA6/C30B fibres was investigated and a strong decrease of the heat release rate was measured. Then, some nanocomposite matrices were used to develop some new kind of fibres: polyamide (PA) [6], poly(butylene terephthalate) (PBT) [7], poly(trimethylene terephthalate) (PTMT) [8], poly(ethylene terephthalate) (PET) [9e11], polypropylene (PP) [12,13] and polyimideamide (PIA) [14,15]. Until now, only few polymer/clay blends have been studied for production of fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the exfoliated morphology was present in both N3 and N5 nanofibers. From TEM results, Yoon et al 8 observed that the nanoclays were better dispersed in the electrospun PA6/MMT fibers than in the pristine PA6/MMT sample. …”
Section: Characterization Of the Electrospinning Nanofibersmentioning
confidence: 99%
“…The addition of MMT, the rapid solvent removal and the ultra-large draw ratio of electrospinning favored the formation of polyamides γ-phase crystallites. Regarding the crystal structures of PA6 and PA6/clay fibers, Yoon et al 8 verified that the annealing increased the γ-crystalline form of both fibers, and its effect was dominant in the PA6/clay fiber. Dn drawing, the γ-crystalline form was easily converted into the α-form in the pure PA6 nanofibers, whereas it was still observed at a relatively high spin-draw ratio in the PA6/clay fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation